Purinergic enzymes on extracellular vesicles: immune modulation on the go - Winzer, Riekje; Nguyen, Du Hanh; Schoppmeier, Felix; Cortesi, Filippo; Gagliani, Nicola; Tolosa, Eva (Frontiers in Immunology, 2024)
An increase in the extracellular concentration of ATP as a consequence of cellular stress or cell death results in the activation of immune cells. To prevent inflammation, extracellular ATP is rapidly metabolized to adenosine, which deploys an anti-inflammatory signaling cascade upon binding to P1 receptors on immune cells. The ectonucleotidases necessary for the degradation of ATP and generation of adenosine are present on the cell membrane of many immune cells, and their expression is tightly regulated under conditions of inflammation. The discovery that extracellular vesicles (EVs) carry purinergic enzyme activity has brought forward the concept of EVs as a new player in immune regulation. Adenosine-generating EVs derived from cancer cells suppress the anti-tumor response, while EVs derived from immune or mesenchymal stem cells contribute to the restoration of homeostasis after infection. Here we will review the existing knowledge on EVs containing purinergic enzymes and molecules, and discuss the relevance of these EVs in immune modulation and their potential for therapy.